Perceptions of cycling helmet safety in relation to sports-related concussion mitigation amongst competitive cyclists - Hurst, H. T.; Anthony Baxter, B. A.; Gamble, T.; Hardwicke, J. (Journal of Science and Cycling, 2022)
Whilst research into competitive cycling and sports-related concussion (SRC) has developed over the past few years, understanding of competitive cyclists` perceptions of helmet safety in relation to mitigating SRC is limited. Therefore, this study aimed to explore these perceptions along with cyclists` attitudes towards seeking medical attention in the event of sustaining helmet damage.